(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the socio-pedagogical necessity of developing artificial intelligence literacy of future teachers of the pedagogical direction. The study reveals pedagogical, ethical and methodological problems arising from the introduction of artificial intelligence tools into the educational process. Based on the views of foreign and national scientists, the role of artificial intelligence literacy in the development of critical thinking, moral responsibility and professional competencies of future teachers is substantiated. The development of a methodology for the formation of artificial intelligence literacy based on a competency-based approach is interpreted as an important task for the modern education system.